Implementasi Pembelajaran Al-Qur’an Melalui Metode Ummi - Rahman Hakim, Arif; Indana, Nurul; Adi Wijono, Hani; Khoirudin Sovwan, Akhmad (ILJ: Islamic Learning Journal, 2025)
This article aims to find out the implementation of learning the Qur'an through the Ummi method at MI Wahid Hasyim Krembangan Gudo Jombang. The research method used in this study is a qualitative research method with a qualitative descriptive research design. Data collection techniques using interviews, observation, and documentation techniques. Furthermore, data analysis was carried out using descriptive analysis methods. The results of this study concluded that: 1. Implementation of Al-Qur'an learning through the Ummi method, namely: (a) Planning in the form of making lesson plans and syllabuses and all teachers must have certification (b) implementation in the form of: Ummi method handbook Stages in learning Learning techniques and learning time Supporting factors, obstacles and solutions in the implementation of Qur'anic learning through the Ummi method consist of: Supporting factors in the implementation of learning the Qur'an through the Ummi method consist of teacher factors, factors of interest and motivation of students, parental factors, the existence of coordinators, facilities and markets. The inhibiting factors in the implementation of learning the Qur'an through the Ummi method consist of, Lack of attention from parents, crowded children's conditions.